Functional characterization of acyl-CoA binding protein in Neospora caninum - Bingxin Zhou; Yong Fu; Heng Zhang; Xianmei Wang; Gaowei Jin; Jianhai Xu; Qun Liu; Jing Liu (Parasites & Vectors, 2020)
Abstract Background Lipid metabolism is pivotal for the growth of apicomplexan parasites. Lipid synthesis requires bulk carbon skeleton acyl-CoAs, the transport of which depends on the acyl-CoA binding protein (ACBP). In Neospora caninum, the causative agent of neosporosis, the FASII pathway is required for growth and pathogenicity. However, little is known about the fatty acid transport mechanism in N. caninum. Methods We have identified a cytosolic acyl-CoA binding protein, with highly conserved amino acid residues and a typical acyl-CoA binding domain in N. caninum. The recombinant NcACBP protein was expressed to verify the binding activities of NcACBP in vitro, and the heterologous expression of NcACBP in Δacbp yeast in vivo. Lipid extraction from ΔNcACBP or the wild-type of N. caninum was analyzed by GC-MS or TLC. Furthermore, transcriptome analysis was performed to compare the gene expression in different strains. Results The NcACBP recombinant protein was able to specifically bind acyl-CoA esters in vitro. A yeast complementation assay showed that heterologous expression of NcACBP rescued the phenotypic defects in Δacbp yeast, indicating of the binding activity of NcACBP in vivo. The disruption of NcACBP did not perturb the parasite’s growth but enhanced its pathogenicity in mice. The lipidomic analysis showed that disruption of NcACBP caused no obvious changes in the overall abundance and turnover of fatty acids while knockout resulted in the accumulation of triacylglycerol. Transcriptional analysis of ACBP-deficient parasites revealed differentially expressed genes involved in a wide range of biological processes such as lipid metabolism, posttranslational modification, and membrane biogenesis. Conclusions Our study demonstrated that genetic ablation of NcACBP did not impair the survival and growth phenotype of N. caninum but enhanced its pathogenicity in mice. This deletion did not affect the overall fatty acid composition but modified the abundance of TAG. The loss of NcACBP resulted in global changes in the expression of multiple genes. This study provides a foundation for elucidating the molecular mechanism of lipid metabolism in N. caninum.